PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, STRUKTUR ASET, PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Permatasari, Melinda; Sulistyo, Sulistyo; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2019)
This study discusses discussing and analyzing company size, profitability, asset structure, sales growth and liquidity towards capital structure, and partially addressing each variable. The population used by mining companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The sampling technique uses a purposive sampling method, so the number of companies sampled is 18 companies. The data used are secondary data consisting of financial statements or financial statements for the year 2015-2017 which can be accessed through www.idx.co.id. The data analysis technique uses multiple linear regression analysis, which previously tested the classical, first tested the hypothesis using a partial test, simultaneous test (F test) and the coefficient of determination.The results of this study indicate company size, profitability, asset structure, sales growth and liquidity simultaneously on capital structure, company partial size, asset structure, and sales growth are positively related to capital structure, so that profitability and liquidity negatively affect capital structure